Concurrent quality and process monitoring with canonical correlation analysis. (December 2017) - Zhu, Qinqin; Liu, Qiang; Qin, S. Joe
Highlights: CCA with regularization is used for quality and process monitoring concurrently. The method retains that efficiency of CCA for quality prediction from process data. CCA is enhanced to exploit the variance using subsequent PCA decompositions. Monitoring statistics are developed for monitoring in respective subspaces. Numerical simulations are used to demonstrate the effectiveness of the method. Abstract: Canonical correlation analysis (CCA) is a well-known data analysis technique that extracts multidimensional correlation structure between two sets of variables. CCA focuses on maximizing the correlation between quality and process data, which leads to the efficient use of latent dimensions. However, CCA does not focus on exploiting the variance or the magnitude of variations in the data, making it rarely used for quality and process monitoring. In addition, it suffers from collinearity problems that often exist in the process data. To overcome this shortcoming of CCA, a modified CCA method with regularization is developed to extract correlation between process variables and quality variables. Next, to handle the issue that CCA focuses only on correlation but ignores variance information, a new concurrent CCA (CCCA) modeling method with regularization is proposed to exploit the variance and covariance in the process-specific and quality-specific spaces. The CCCA method retains the CCA's efficiency in predicting the quality while exploiting the variance structure for quality and process monitoring using subsequent principal component decompositions. The corresponding monitoring statistics and control limits are then developed in the decomposed subspaces. Numerical simulation examples and the Tennessee Eastman process are used to demonstrate the effectiveness of the CCCA-based monitoring method.